Modernization of Islamic Education Learning Ahmad Tafsir Perspective - Muhamad Basyrul Muvid; Ahmad Taufik (Maharot : Journal of Islamic Education, 2022)
This study aims to examine and analyze more deeply the idea of modernizing Islamic religious education learning in the style of Ahmad Tafsir. The research method used is literature by collecting various reference sources, books, articles, documents related to the topic of study. It can be concluded that the modernization of Islamic religious education learning from Ahmad Tafsir's perspective emphasizes collaboration and integration between spiritual, intellectual and moral intelligence. Considering that these three intelligences are the basic capital for graduates of Islamic religious education, so that they can actualize all their potential in the midst of community life that is supported by high morality and spirituality. Thus, all the abilities and talents of students who are forged during learning do not come out of the ethical values of the Islamic religion itself.